When Instructors Self-Disclose but Misbehave: Conditional Effects on Student Engagement and Interest. Issue 5 (19th October 2016) - Borzea, Dana; Goodboy, Alan K.
Abstract : This study examined the conditional influence of relevant instructor self-disclosure on student interest (cognitive, emotional) and engagement (silent-in-class, oral-in-class, thinking about course content, out-of-class). College student participants ( N = 169) completed a questionnaire on their instructor's disclosures and misbehaviors in class, and their own interest and engagement in a college course. The positive associations between relevant instructor self-disclosure with student interest and engagement were conditional; they were moderated by perceived instructor misbehaviors (antagonism, lectures). Overall, the positive associations were diminished for cognitive and emotional interest when instructors were antagonistic; these associations became nonsignificant, and then negative at higher levels of antagonism. Similarly, the positive associations were diminished for all four types of student engagement when instructors delivered boring and confusing lectures; these associations became nonsignificant at higher levels of lecture misbehaviors, and the associations for silent in-class and out-of-class engagement became negative at very high levels of lecture misbehaviors.